Optimized error protection of scalable image bit streams [advances in joint source-channel coding for images]. - Hamzaoui, R. (IEEE Signal processing magazine)
This article focuses on FEC for scalable image coders. For various channel models, we survey recent progress made in system design and discuss efficient source-channel bit allocation techniques, with emphasis on unequal error protection. This article considered JSCC (joint source-channel coding) at the application layer only. Recent research has studied cross-layer optimization where JSCC is applied to both the application layer and the physical layer. The basic task here is to minimize the average distortion by allocating available power, subcarriers, and bandwidth among users at the physical layer and source-channel symbols at the application layer subject to a total resource constraint. Most of the JSCC systems covered in this article can be readily extended to transmit scalable compressed bit streams of video sequences and 3-D meshes. Due to the stringent delay constraints in video communications and the fact that MPEG is currently exploring a scalable video coding standard, fast JSCC algorithms are expected to play a bigger role and bring more performance gains. This article is also expected to stimulate further research efforts into JSCC and more importantly, prompt the industry to adopt some of these JSCC algorithms in their system designs, thus closing the cycle from algorithm development to implementation.